Plasma and Aorta Biochemistry and MMPs Activities in Female Rabbit Fed Methionine Enriched Diet and Their Offspring - Khira Othmani Mecif; Souhila Aouichat Bouguerra; Yasmina Benazzoug (Journal of Nutrition and Metabolism)
This study investigated whether a high Met diet influences biochemical parameters, MMPs activities in plasma, and biochemical and histological remodeling in aorta, in both pregnant female rabbits and their offspring. Four female rabbit groups are constituted (each n=8), nonpregnant control (NPC), pregnant control (PC) that received normal commercial chow, nonpregnant Met (NPMet), and pregnant Met (PMet) that received the same diet supplemented with 0,35% L-methionine (w/w) for 3 months (500 mg/d). All pregnant females realize 3 successive pregnancies. Plasma results showed that Met excess increased Hcy, raised CRP in NPMet and decreased it in PMet, enhanced significantly proMMP-2 and proMMP-9 activities in NPMet, and reduced them in PMet. Aorta showed a rise in collagen level, essentially in PMet, a reduction of elastin content in both PMet and NPMet, and a significant decrease in lipid content in PMet, with histological changes that are more pronounced in NPMet than PMet. Met excess enhanced proMMP-9 activities in NPMet while it decreased them in PMet. PMet newborn presented increase in uremia and CRP and significant rise of active MMP-2 and MMP-9 forms. In aorta, media and adventitia thickness increased, total lipids content decreased, proMMP-9 activity decreased, and proMMP-2 activity increased.